Posicionamento ótimo de múltiplos sinks móveis em redes de sensores sem fio: uma proposta para cidades inteligentes - Oliveira, Emerson Santos de (2018)
The development of new technologies in the last years in the areas of wireless commu- nications has brought many advantages to the development of many sectors of the city. Recent advances in sensor technology are providing an expansion of the possible appli- cations, creating an environment of increasingly efficient data communication. With this, we can see a great advance in the scientific researches related to the development of te- chniques and improvement of communication in Wireless Sensor Networks (WSN). In fact, this type of network has been applied in several areas, such as: smart cities, internet of things (IoT), environmental monitoring, Vehicle tracking, health applications, among others. In this context, this work proposes to develop an algorithm for positioning node sinks in urban areas for intelligent cities, in order to optimize the communication between mobile sink nodes and fixed sensors clustered in a WSN. This approach allows the opti- mization of WSN for the urban environment, providing an improvement in the rates of energy consumption, processing and transmission of data in the network.